Angiographic Findings in Refractory Delayed Cerebral Ischemia - González, Nicolás; Ruiz, Alvaro; Mura, Jorge (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2019)
Background Delayed cerebral ischemia (DCI) follows a refractory course in a subgroup of patients with aneurysmal subarachnoid hemorrhage (SAH), leading to diffuse ischemic injury. The role of angiographic vasospasm (AV) is unknown. Our goal is to study the angiographic alterations and the clinical profile of refractory DCI patients.Methods Retrospective study of patients with SAH who presented with DCI treated with medical and endovascular therapy, with a refractory evolution, defined as multiple ischemic infarction and brain death.Results Out of a cohort of 336 patients, 7 (2%) developed refractory DCI. The median age of the patients was 48 (38–60) years old. Five patients had ruptured anterior communicating artery (ACoA) aneurysms. Four patients were treated with coil embolization, and three with microsurgical clipping. Angiographic vasospasm was classified as severe in 5 cases. Compromise of bilateral circulation was detected in six patients. Distal circulation vasospasm occurred in five cases. Slow circulatory transit times were observed in three patients.Conclusion Angiographic findings such as bilateral circulatory compromise and distal vasospasm were frequent alterations. Further studies are required to establish the association of these findings with the clinical outcomes.
Keywords: subarachnoid hemorrhage; intracranial vasospasm; brain ischemia; angioplasty